The Use of Technology in Distance Language Learning - Núñez Núñez, Graciela (2008)
Distance language learning is a real challenge to both teachers and learners, since the students’ exposure to the target language in a distance learning system is not as authentic and interactive as required. Additionally, it also entails a significant reduction in the amount of students’ interaction and in the support from both the teacher and other learners, which has a negative impact on students’ levels of motivation and achievement. In the hope of enhancing the distance teaching-learning process of a language and compensating for the previously mentioned drawbacks, a number of technological tools are currently being implemented. However, these technologies have also brought about new challenges that need to be addressed by policy makers, materials developers, teachers and students, if they are to be successfully implemented.